The Corpus as Tutor: Data-driven Persuasive Language Learning - Winther-Nielsen, Nicolai (HIPHIL Novum, 2017)
This paper presents a new persuasive technology that uses a corpus stored in a database to generate learning objects for tutoring of self-directed learning. The technology was developed within the European Union project EuroPLOT 2010-2013 in order to drive effective learning through technology with, in, and around a corpus application. The paper argues that a corpus can generate learning objects, but a theory of Persuasive Technology must to be applied to optimise the design for learning. The paper presents Bible Online Learner as the implementation of this new architecture for persuasive corpus-driven learning, persuading the learner to focus on the form of the text through the interface and then guiding the learner into practice authentic forms. The corpus used is a database of the Hebrew Bible created by the EepTalstra Centre for Bible and Computer at the VU University in Amsterdam for and called ETCBC4.